BREAD FEEDS THE BODY, AND BOOKS FEED THE MIND - A. I. Karimova (Ecominds Press, 2025)
The article emphasizes the importance of instilling a love for reading in children from an early age and highlights the need to organize reading competitions and stage performances based on literary works—not only in schools but also in all institutions of higher education. Thanks to these efforts, young people develop not only articulate and expressive speech and the ability to clearly and confidently express their thoughts, but they are also brought up through books. In other words, our children grow into intelligent, highly moral, kind, and decent individuals—those to whom we can entrust our future.
Keywords: Leader, activist, imagination, fantasy, videos, memes, podcasts, platforms like Wattpad and Amazon Kindle.